Problem of Empirical Basis of Scientific Knowledge in the Philosophy of the 20th Century - Valevičius, Vytautas (Problemos, 1982)
The present article analyses some problems of the contemporary theory of science. The author distinguishes two trends in the theory of science. Further the article discusses the ways of solving the problem of the relation between empirical data and theory by the two trends. Finally, an attempt is made to find a Marxist solution of this problem.